Reducing wind-induced vibrations of road sign structures through aerodynamic modifications: A computational pilot study for a practical example. Issue 199 (April 2020) - Zhu, Qiming; Stoter, Stein K.F.; Heisel, Michael; French, Catherine E.; Guala, Michele; Linderman, Lauren E.; Schillinger, Dominik
Abstract: In this article, we illustrate the potential of aerodynamic modifications of road signs to reduce wind-induced vibrations. Using a real-world sign structure operated by the Minnesota Department of Transportation, we focus on two modification variants, one based on the simple removal of secondary panels and one based on the addition of drag reducing rear extensions to the main panel. Our main analysis tool is a computational fluid dynamics framework based on the finite element method, which is validated against experiments with a scaled sign model that were conducted in the towing tank and the wind tunnel of the St. Anthony Falls Laboratory. We demonstrate computationally that aerodynamic modifications constitute an effective way of reducing the vibration amplitude in the example structure for head wind at the average operating wind speed. The present study can be seen as a first step towards establishing the use of aerodynamic devices for road sign structures. Highlights: Potential of aerodynamic modifications of road signs to reduce wind-induced vibrations is explored computationally. The CFD analysis tool based on the finite element method is validated with experiments. Effective modifications minimize drag and control aerodynamic admittance. The need for detailed studies that take into account aeroelastic effects is highlighted.